2021
DOI: 10.3390/ani11041162
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory and Feeding Behavior under Different Management and Heat Stress Conditions in Heifer Water Buffalo (Bubalus bubalis) in the Tropics

Abstract: In the wake of climate change and global warming, the production systems of water buffaloes (Bubalus bubalis) are receiving increasing attention in the tropics, where the silvopastoral systems can improve animal welfare and production conditions. The objective of this study was to characterize the behavior of heifer buffaloes in a silvopastoral system (SPS) with Leucaena leucocephala (600 trees/ha) and in a conventional system (CVS), under intense heat stress and moderate heat stress in Cuba. We observed nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Recently, silvo-pastoral systems have been proposed as an alternative method to conventional breeding [ 101 , 102 ]. Athaide et al [ 101 ] comparing two herds of buffalo reared one under a silvo-pastoral system (SPS) and the other one under a conventional system (CVS, pens with no shade) and found that subjects in the CVS had higher RT, ST, and HR.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, silvo-pastoral systems have been proposed as an alternative method to conventional breeding [ 101 , 102 ]. Athaide et al [ 101 ] comparing two herds of buffalo reared one under a silvo-pastoral system (SPS) and the other one under a conventional system (CVS, pens with no shade) and found that subjects in the CVS had higher RT, ST, and HR.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…Athaide et al [ 101 ] comparing two herds of buffalo reared one under a silvo-pastoral system (SPS) and the other one under a conventional system (CVS, pens with no shade) and found that subjects in the CVS had higher RT, ST, and HR. Galloso-Hernández et al [ 102 ] carried out a study on heifers under two rearing systems: SPS and CVS. They reported that in the SPS, the ambient temperature was 2 °C lower than in the CVS (33.01 vs. 31.00 °C), and the feeding behavior (time spent eating, ruminating, and drinking water) was greater in the SPS under intense HS conditions (>75 THI).…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…As previously stated for other ruminants, there is a growing interest in silvopastoral systems in buffalo husbandry. Water buffalo RT (visually assessed from 0600 to 1800 h) did not differ among heifers in different HS conditions under conventional or silvopastoral systems; however, this evaluation was evidenced in a very limited number of heifers (n = 9) and for a limited daytime (Galloso-Hernańdez et al, 2021). The same small sample size was reported in a previous study by the same researchers (Galloso-Hernańdez et al, 2020), but with a significant increase of RT (0600 to 1800 h) in moderate HS compared to intense HS, confirming the "adaptation strategy" already well described in cows (Calamari et al, 2014;Abeni and Galli, 2017).…”
Section: Rumination In Extensive Agroforestry and Silvopastoral Systemsmentioning
confidence: 75%
“…However, it is important to consider that buffaloes that graze freely on flooded land are more susceptible to endoparasites (fasciolosis and schistosomiasis), leptospirosis, Brucellosis, among other diseases such as mastitis, causing an economic impact due to low production, high mortality, and a threat to public health [28,40]. Finally, it is important to point out that buffalo can be productively efficient without the need to express their thermoregulatory behavior, as long as this natural behavior is substituted with the provision of natural or artificial shade and in an environment very close to the thermoneutral zone, as has been reported previously [38,41].…”
Section: Characterization Of the Productive Unitsmentioning
confidence: 87%